Teaching English and Plus Curriculum: Teachers’ Challenges and Strategies in an Indonesian Madrasah - Erlina, Dian; Marzulina, Lenny; Holandyah, Muhammad; Herizal, Herizal; Harto, Kasinyo; Putri, Hikmah Zalifah; Sari, Iin Puspa (Universitas Jambi, Indonesia, 2024)
This qualitative case study aimed to investigate teachers’ challenges and strategies in teaching English as a foreign language using a Plus curriculum, a self-designed curriculum that combines the national curriculum and the Pesantren (Islamic boarding school) curriculum. This study involved two English teachers at a private Indonesian Madrasah Aliyah (Islamic Senior High School) in Ogan Ilir Regency, South Sumatra, Indonesia. Data were collected through in-depth interviews and analyzed using thematic analysis. The research revealed several internal and external challenges encountered by the teachers when teaching English using this combined curriculum. Internal challenges included three aspects: teachers' abilities to utilize ICT in teaching, designing lesson plans, and enhancing students' learning motivation. External challenges included two aspects: managing limited time allocation and dealing with inadequate learning facilities. Despite these teaching challenges, the researchers identified several strategies employed by the teachers to overcome the challenges. These strategies include improving their practical knowledge in using ICT, tailoring teaching materials and methods with learning objectives, applying various motivational strategies, providing extra time for informal learning after school, and ensuring students’ access to necessary learning facilities and resources.